Arabidopsis AtDjA3 Null Mutant Shows Increased Sensitivity to Abscisic Acid, Salt, and Osmotic Stress in Germination and Post-germination Stages - Salas-Muñoz, Silvia; Rodríguez-Hernández, Aída A.; Ortega-Amaro, Maria A.; Salazar-Badillo, Fatima B.; Jiménez-Bremont, Juan F. (Frontiers in Plant Science, 2016)
DnaJ proteins are essential co-chaperones involved in abiotic and biotic stress responses. Arabidopsis AtDjA3 gene encodes a molecular co-chaperone of 420 amino acids, which belongs to the J-protein family. In this study, we report the functional characterization of the AtDjA3 gene using the Arabidopsis knockout line designated j3 and the 35S::AtDjA3 overexpression lines. Loss of AtDjA3 function was associated with small seed production. In fact, j3 mutant seeds showed a reduction of 24% in seed weight compared to Col-0 seeds. Expression analysis showed that the AtDjA3 gene was modulated in response to NaCl, glucose, and abscisic acid (ABA). The j3 line had increased sensitivity to NaCl and glucose treatments in the germination and cotyledon development in comparison to parental Col-0. Furthermore, the j3 mutant line exhibited higher ABA sensitivity in comparison to parental Col-0 and 35S::AtDjA3 overexpression lines. In addition, we examined the expression of ABI3 gene, which is a central regulator in ABA signaling, in j3 mutant and 35S::AtDjA3 overexpression lines. Under 5 μM ABA treatment at 24 h, j3 mutant seedlings displayed higher ABI3 expression, whereas in 35S::AtDjA3 overexpression lines, ABI3 gene expression was repressed. Taken together, these results demonstrate that the AtDjA3 gene is involved in seed development and abiotic stress tolerance.